STRATEGI BERSAING MASKAPAI PENERBANGAN CITILINK INDONESIA - Warnanti, Asri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
The purpose of this study was to determine the effect of pricing strategies and service quality on purchasing decisions for Citilink Indonesia airline tickets. The research design used in compiling this research is quantitative with descriptive explanations. The analytical method used is multiple linear regression analysis with a sample of 98 and the sampling technique used is the Accidental Sampling. Hypothesis test results show that the price has a positive and significant effect on purchasing decisions of 0.510 and t arithmetic 5.484. Quality of service has a positive and significant effect on purchasing decisions of 0.258 and t count 2.768. The results of the regression analysis prove there is a simultaneous influence of price strategy and service quality variables together proven to have a positive and significant effect on purchasing decisions with a contribution of 47.7% while the remaining 52.3% is explained by other variables outside this study